A Distributed Two-Stage Economic Dispatch for Virtual Power Plant Based on An Improved Exact Diffusion Algorithm - Zheng, Yingxuan; Wang, Zhen; Ju, Ping; Wu, Hao (Frontiers in Energy Research, 2021)
To manage a large scale of distributed energy resources (DERs) dispersed geographically and reduce the impact of DER uncertainties, this paper proposes a distributed two-stage economic dispatch for virtual power plant (VPP) to track a specified VPP schedule curve. In the look-ahead stage, a distributed economic dispatch strategy is proposed to optimally allocate the scheduled power among DERs. In the real-time stage, a distributed VPP schedule curve tracking problem is modeled to balance the fluctuation of wind farms and/or PV stations. The two-stage distributed optimization problems are solved by an improved exact diffusion algorithm which is proved to be robust to local communication failure. Case studies validate the performance of the algorithm proposed.